A poesia de Amélia Rodrigues nas aulas de língua portuguesa - Silveira, Jeane Mota da Silva (2019)
The present paper is based on the Intervention Project, “A poesia de Amélia Rodrigues nas aulas de Língua Portuguesa” (The Amélia Rodrigues’ Poetry in the Portuguese Language classes), linked to the Professional Master in Academy of Letters of the Universidade Estadual de Feira de Santana. The research was applied to students of the 8° grade of the elementary education, of a school published located in Amélia Rodrigues City, in Bahia, with the intent to contribute for reader formation of these students and to encourage the critical thoughts that have as aim the sociocultuals and identities aspacts. Intending to facilitate, onwards the Reading of the literatures texts of the local author, Amélia Augusta Rodrigues, a relation between historical questions prominent of the socialcultural context, which is inserted this literary work, we estabilished an association with the students current environment. As of the lack of interest observation for Reading of literature texts diagnosed in these students, and mainly by the understanding that they, while being inhabitants of the Amelia Rodrigues City, do not know the author’s in this study representativeness, we dicided to the elaboration of this work. With this in mind, we developed with these students literacy practices in orther to bring them closer to literature text Reading, and to contribute to the enlargement of the text comprehention capability. In this regard, we used digital and virtual tools of teaching, that frequently present in these students’ daily, we considered it as an effective intrument to encourage them to read litereture text. We decided to use the digital platform Wordpress, site https://professorajeaneblog.wordpress.com/ developping, through a collaborative contruction, a digital asset which we gathered a part of this author literary production, that is diperse along the country. Furthermore, this research was conducted too, with the intention of gathering the literary work that is not available for students in libraries. So, for insert the local literature in the Portuguese classes, we objectified the appreciation of the literary memory of this writer whom contributed for historical formation of this town and of these individuals, and to enable the insertion, by significant form, of the literate pratictices of the knowledges in this educational context.